2022
DOI: 10.1055/s-0042-1755389
|View full text |Cite
|
Sign up to set email alerts
|

Serum SCUBE-1 Levels and Return of Spontaneous Circulation Following Cardiopulmonary Resuscitation in Adult Patients

Abstract: Background SCUBE 1-has been used as a biomarker for the diagnoses of myocardial infarction, stroke, mesenteric ischemia, and gastric cancer in some recent studies. In this study, we investigated the relationship between serum SCUBE−1 levels and return of spontaneous circulation (ROSC) in patients who received cardiopulmonary resuscitation (CPR). Methods Patients over 18 years of age who were not pregnant and received CPR were divided into two groups: those who achieved ROSC and those who died. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…ROSC occurs when the heart regains an effective and sustainable rhythm, leading to the restoration of spontaneous blood circulation. Achieving ROSC is a critical milestone as it indicates that the interventions have been successful in reviving the patient (5). The chances of achieving ROSC are significantly influenced by the timeliness and effectiveness of the interventions.…”
Section: Cardiopulmonary Resuscitationmentioning
confidence: 99%
See 1 more Smart Citation
“…ROSC occurs when the heart regains an effective and sustainable rhythm, leading to the restoration of spontaneous blood circulation. Achieving ROSC is a critical milestone as it indicates that the interventions have been successful in reviving the patient (5). The chances of achieving ROSC are significantly influenced by the timeliness and effectiveness of the interventions.…”
Section: Cardiopulmonary Resuscitationmentioning
confidence: 99%
“…Early initiation of CPR, prompt defibrillation, and coordinated advanced life support measures substantially increase the likelihood of ROSC. However, even with successful ROSC, the underlying cause of the cardiac arrest must be identified and addressed to prevent a recurrence (4,5).…”
Section: Cardiopulmonary Resuscitationmentioning
confidence: 99%
“…In this way, it has been reported that adromedullin may be a shortterm mortality predictor in sepsis based on hazard ratio of 2.6 (17). SCUBE-1 is a peptide synthesized from platelets and associated with thrombosis, hypoxia and inflammation (18,19). Increased SCUBE-1 concentrations in the systemic circulation are associated with mortality in sepsis based on AUC of 0.813 with a specificity of 75.6%, a sensitivity of 81.3%, and a cutoff value of ≥4,73 (20).…”
mentioning
confidence: 99%
“…SCUBE-1 accumulation was detected immunohistochemically in the subendothelial matrix of advanced atherosclerotic lesions in humans. SCUBE-1 is thought to be a new platelet adhesion molecule (5). Recent studies have revealed that SCUBE-1 expression is increased in patients with acute coronary syndrome and acute large vessel atherothrombotic stroke.…”
mentioning
confidence: 99%